PERANAN SEKTOR UNGGULAN TERHADAP PEREKONOMIAN DI KABUPATEN JAYAWIJAYA - Epra ., Wenda; O. Esry H. Laoh; Melissa L. G. Tarore (Sam Ratulangi University, 2018)
This study aims to determine what sectors are the leading sectors and the role of superior sector to the economy within the last 5 years in Jayawijaya regency. This research is conducted for three months starting from June 2017 until August 2017 in Jayawijaya Regency. The data used in this study is secondary data obtained from the Central Bureau of Statistics (BPS) Jayawijaya district. The data is in though using descriptive analysis research method. The research shows that the sectors that are the leading sectors in Jayawijaya Regency are agriculture, forestry, fishery, processing industry sector, electricity, gas and water supply sector, construction sector, trade, hotel and restaurant sector, transportation and communications sector, and the services sector. The sectors of services, transport and communications, and the agricultural sector are the most contributing sectors in the economy compared to other leading sectors.